Business Plans Handbook : A Compilation of Actual Business Plans Developed by Small Businesses Throughout North America. - Kahrs, Kristin, editor 415379; Gale Group (Online service) 651863 (Detroit, MI : Gale, 1993)
Collection of actual business plans from businesses in the manufacturing, retail and service industries, with company names and addresses changed. Includes: business plan template, fictional business plans, listing of organizations, agencies, and consultants; a glossary; and an updated bibliography. Aimed at entrepreneurs seeking funding for small businesses in North America.